ENHANCING LEGAL POLICIES IN THE LOGISTICS SECTOR IN THE CONTEXT OF INTERNATIONAL INTEGRATION IN VIETNAM - Phuong, Le Thi Nam (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study assesses and suggests enhancements to the legal framework governing the logistics sector in Vietnam, particularly in light of its integration into the global economy. The research begins by examining Vietnam’s strategic position in the global supply chain and the significant potential of the logistics industry, along with current challenges such as high costs and uneven infrastructure. The analysis then continues by reviewing the existing legal policy framework, including laws, decrees, and regulations, emphasizing the importance of issuing comprehensive and context-appropriate policies aligned with the industry’s development reality. The concept of "green logistics" is highlighted as a development trend, with Vietnam having signed and implemented various Free Trade Agreements, supporting enhanced trade connections and international standard integration. The study also identifies deficiencies in the current policy system and suggests improvements through the issuance of relevant and timely policy documents, along with the development of sustainable seaports. The research concludes that perfecting legal policies for the logistics sector is essential to promote its sustainable development in Vietnam.